THE EFFECT OF INFORMATION GAP ACTIVITIES ON STUDENTS' SPEAKING SKILL (A Study at the Eleventh Grade Students' of SMA Negeri 1 Sibabangun in 2019/2020 Academic Year) - Dewi Sartika Nasution (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aim of this research are to know: 1) The extent of the application of information gap activities on students' speaking skill at the eleventh grade students of SMA Negeri 1 Sibabangun, 2) The extent of the student speaking skill before and after using information gap activities at the eleventh grade students of SMA Negeri 1 Sibabangun., 3) Whether there is any significant effect of using information gap activities on students' speaking skill at the eleventh grade students of SMA Negeri 1 Sibabangun. This research uses experimental method with true-experimental research design; post-test only control-group design. The population of this research is all of the eleventh grade students SMA Negeri 1 Sibabangun which consist of 196 students. Sample were 64 students which taken by simple random sampling. In collecting the data, the researcher uses observation sheet and test as an instrument. The result of the research: 1) The application of information gap activities is 3.5, it is categorized "Very Good". 2) The mean score of the students' speaking skill is 53.5, it is categorized "Less". Meanwhile after using information gap activities was 72.68, it is categorized "Good". The result of data analysis shows that ttest is higher than ttable (ttest 13.78 > ttable2.04). So, the hypothesis is accepted. It means that, 3) There is a significant effect of information gap activities on students' speaking skill at the eleventh grade students of SMA Negeri 1 Sibabangun in 2019/2020 Academic Year.